Wall teichoic acids are dispensable for anchoring the PNAG exopolysaccharide to the Staphylococcus aureus cell surface - Vergara-Irigaray, Marta; Maira-Litran, Tomas; Merino, Nekane; Pier, Gerald B.; Penadés, José R.; Lasa, Inigo (2017)
Biofilm formation in Staphylococcus aureus is usually associated with the production of the poly-N-acetylglucosamine (PNAG) exopolysaccharide, synthesized by proteins encoded by the icaADBC operon. PNAG is a linear beta-(1-6)-linked N-acetylglucosaminoglycan that has to be partially deacetylated and consequently positively charged in order to be associated with bacterial cell surfaces. Here, we investigated whether attachment of PNAG to bacterial surfaces is mediated by ionic interactions with the negative charge of wall teichoic acids (WTAs), which represent the most abundant polyanions of the Gram-positive bacterial envelope. We generated WTA-deficient mutants by in-frame deletion of the tagO gene in two genetically unrelated S. aureus strains. The Delta tagO mutants were more sensitive to high temperatures, showed a higher degree of cell aggregation, had reduced initial adherence to abiotic surfaces and had a reduced capacity to form biofilms under both steady-state and flow conditions. However, the levels as well as the strength of the PNAG interaction with the bacterial cell surface were similar between AtagO mutants and their corresponding wild-type strains. Furthermore, double Delta tagO Delta icaADBC mutants displayed a similar aggregative phenotype to that of single Delta tagO mutants, indicating that PNAG is not responsible for the aggregative behaviour observed in Delta tagO mutants. Overall, the absence of WTAs in S. aureus had little effect on PNAG production or anchoring to the cell surface, but did affect the biofilm-forming capacity, cell aggregative behaviour and the temperature sensitivity/stability of S. aureus.